Food hygiene practices among food handlers of food truck in Malaysia / Nur Izzati Ibrahim & Noorizzati Ismail - Ibrahim, Nur Izzati; Ismail, Noorizzati (2017)
Food truck nowadays is slowly gaining its popularity in Malaysia. Although food truck is only available in certain places in Malaysia, it is still famous and influencing. Food trucks are different from restaurants where by they sell food on the truck. One example o f food truck in Malaysia which we are all familiar with is the ice - cream truck at night markets and street stalls. The most important thing about food truck is the food hygiene practices among its food handlers whenever they serve their customers. This study will focus on the food hygiene practices o f food truck handlers as unnecessary contamination that could occur. The researchers are also looking at the hygiene level o f the food as well as the safety of the food in the truck, as there are lower complaints lodged about the food truck hygiene. People in Malaysia are most likely to choose food trucks because the price is reasonable and it saves time to find a selection o f delicious food to eat.